Analisis Pendapatan Usaha Ikan Asin di Kelurahan Sumber Jaya Kecamatan Kampung Melayu Kota Bengkulu - Duharman Duharman; Siltia Ninda Herlianti (Universitas Dehasen Bengkulu, 2022)
This study aims to find out how much income from salted fish business in Sumber Jaya Village, Kampung Melayu District, Bengkulu City. This type of research is descriptive research. The subjects in this study were 21 salted fish business people in Sumber Jaya Village, Kampung Melayu District, Bengkulu City. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data processing, data analysis, interpretation of the results of the analysis. The results of this study found that the capital used in the salted fish business is own capital. The raw materials for this business are fresh sea fish and salt. The production costs in the salted fish business include the cost of production facilities, equipment depreciation costs, labor costs and other costs. The income of salted fish business in Sumber Jaya Village, Kampung Melayu Subdistrict, Bengkulu City in 1 month is the smallest, namely Rp. 3,619,304 and the largest is Rp. 5,707,304. The average income of salted fish business is RP 4,663,304..